TINJAUAN YURIDIS TINDAK PIDANA PENGANIAYAAN BERENCANA YANG DIPUTUS PASAL 351 AYAT 2 KUHP (PUTUSAN NOMOR 155/PID.B/2021/PN KDL): Juridical Review Of The Planned Criminal Action Decisioned Article 351 Paragraph 2 Of The Criminal Code (Decision Number 155/Pid.B/2021/Pn Kdl) - Bastari, Fuad Ahil; Tawang, Dian Adriawan Daeng (Faculty of Law, Universitas Trisakti, 2024)
The title of this research is